Prevalence of Vaginal Infections in Preterm Labour - Rakhshinda Inam Khan, Bushra Bashir, Shahnaz Sultan, Hajra Rafique, Asifa Alia, Sanila Gul (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the association of vaginal infection in preterm deliveries. Study Design: Retrospective/prospective study Place and Duration: Gynaecology and Obstetrics department of MSF Women’s Hospital Peshawar and King Abdullah Teaching Hospital, Mansehra for the duration of six months form August 2021 to January 2022. Methods: Total 76 females with ages 18-(42) years were presented in this study. After receiving informed written consent, detailed demographic information about the enrolled patients, such as age, body mass index, domicile, and educational status, was recorded. Gravidity status and history of preterm deliveries were also assessed among all cases. Association of microorganisms was diagnosed by taking high vaginal swab and sent for test in bio lab. Prevalence of vaginal infections and risk factors were calculated. SPSS 23.0 was used to analyze all data. Results: Among all, 40 (52.6%) were ages between 18-28 years, 22 (28.9%) had age 29-38 years and 14 (18.4%) patients were aged between 39-48 years. Majority females 55 (72.4%) had BMI <25kg/m2 and 21 (27.6%) had BMI >25kg/m2. As per socio-economic status, 44 (59.2%) cases had poor, 20 (26.3%) cases had middle and 12 (15.8%) patients were from upper class. There were 27 (35.5%) patients had history of preterm deliveries. Frequency of vaginal infections was found in 28 (36.8%) cases. UTI was found in 22 (28.9%) patients. Among HVS culture test, candida found in 25 (35.9%) patients. E.coli was the most common micro-organism found in 10 (13.2%) patients. Conclusion: This study led us to the conclusion that vaginal infections greatly contribute to the unnecessary causes of premature labour. Screening for asymptomatic genitourinary infections in pregnant women is always a good idea. Early diagnosis and timely treatment of vaginal infections help reduce preterm labour and the related neonatal morbidity and mortality of premature newborns. Keywords: Vaginal Infections, UTI, Preterm Delivery, E.coli